Cicerone in Seneca: alcune riflessioni su un tema sempre attuale (con un’Appendice su: Cicerone gradarius in Seneca ep. 40, 11) - Cicero in Seneca: Select Reflections on an Ever Current Topic (with an Appendix on: Cicero the gradarius in Seneca Ep.40,11) - Rita Degl'Innocenti Pierini (Ciceroniana On Line)
This paper examines several aspects of the complex relationship between Seneca philosophus and Cicero. In the first place, I review a selection of Seneca’s Letters (in particular, 21; 40; 100; 107; 114; 118), drawing a focus around Seneca’s judgments of Cicero’s style and corpus. I then analyse the portrait of Cicero sketched in Brev. Vit. 5, where Seneca develops a concept of libertas that differs significantly from that set out in the letters and that in turn underscores Seneca’s inability to comprehend the republican political reality. An appendix is dedicated to the examination of the epithet gradarius used to describe Cicero in Ep. 40, 11, in context of equine metaphors applied to his literary style.